Differences in color learning between pollen- and sucrose-rewarded bees - Nicholls, Elizabeth K (Commun Integr Biol, 2015)
What bees learn during pollen collection, and how they might discriminate between flowers on the basis of the quality of this reward, is not well understood. Recently we showed that bees learn to associate colors with differences in pollen rewards. Extending these findings, we present here additional evidence to suggest that the strength and time-course of memory formation may differ between pollen- and sucrose-rewarded bees. Color-naïve honeybees, trained with pollen or sucrose rewards to discriminate colored stimuli, were found to differ in their responses when recalling learnt information after reversal training. Such differences could affect the decision-making and foraging dynamics of individual bees when collecting different types of floral rewards.